PENYULUHAN VAKSINASI COVID-19 PADA ANAK DAN VAKSIN BOOSTER DEWASA - Dewi Perwito Sari; Asri Wido Mukti; Laila Magfiroh I Suwarso; Reza Widya Putri; Ira Purbosari (Universitas Kristen Immanuel, 2022)
Covid-19 is a disease caused by the SARS-CoV-2 virus that has occurred since 2019. Based on observations of longer-term clinical trials, it shows that the immune response produced by the COVID-19 vaccine will decrease over time with varying intervals of decline depending on the type of vaccine. The vaccine given is a booster vaccination/advanced dose to maintain the immunogenicity of the vaccine against COVID-19 infection. From the results of these studies, it can be concluded that the Covid 19 vaccine is safe and provides a good immune response in children. This service is carried out with the aim of providing knowledge and socializing the covid 19 vaccination to children and booster to adults to the community.